2004
DOI: 10.1152/ajpregu.00295.2004
|View full text |Cite
|
Sign up to set email alerts
|

5-HT3receptors participate in CCK-induced suppression of food intake by delaying gastric emptying

Abstract: Hayes, Matthew R., Rachael L. Moore, Samit M. Shah, and Mihai Covasa. 5-HT 3 receptors participate in CCK-induced suppression of food intake by delaying gastric emptying. Am J Physiol Regul Integr Comp Physiol 287: R817-R823, 2004. First published June 10, 2004 10.1152/ajpregu.00295.2004.-Serotonin type 3 (5-HT 3) receptors have been shown to participate in the negative-feedback control of food intake. We previously reported that cholecystokinin (CCK)-induced suppression of food intake is partly mediated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 57 publications
(73 reference statements)
6
43
1
2
Order By: Relevance
“…In these experiments, CCK and 5-HT synergistically reduced food intake in a supra-additive manner, suggesting that CCK and 5-HT together bring about a stronger satiety signal than each system alone [245]. Data from the same group shows that the effects of the 5-HT3 antagonist depends on gastric signals, as gastric distension is required and the CCK antagonist, in contrast to CCK itself, is ineffective in sham-fed rats [206]. The involvement of hindbrain 5-HT3 receptors in CCK-induced satiation has been demonstrated [107].…”
Section: -Ht Interactions With Cck and Leptinmentioning
confidence: 76%
See 2 more Smart Citations
“…In these experiments, CCK and 5-HT synergistically reduced food intake in a supra-additive manner, suggesting that CCK and 5-HT together bring about a stronger satiety signal than each system alone [245]. Data from the same group shows that the effects of the 5-HT3 antagonist depends on gastric signals, as gastric distension is required and the CCK antagonist, in contrast to CCK itself, is ineffective in sham-fed rats [206]. The involvement of hindbrain 5-HT3 receptors in CCK-induced satiation has been demonstrated [107].…”
Section: -Ht Interactions With Cck and Leptinmentioning
confidence: 76%
“…Inducing satiety by intraduodenal fat infusion could only fully be blocked when the CCK-1 antagonist devazepide and the 5-HT3 antagonist tropisetron were administered together [242]. Such interactions between CCK and 5-HT3 antagonists have later been shown for intake of sucrose solution and also of a solid diet [206,243,244]. In these experiments, CCK and 5-HT synergistically reduced food intake in a supra-additive manner, suggesting that CCK and 5-HT together bring about a stronger satiety signal than each system alone [245].…”
Section: -Ht Interactions With Cck and Leptinmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Gastric emptying was measured using dyedilution spectrophotometry. 41 Inhibition for food intake and gastric emptying in response to peripheral Ex-4 was comparable to intact control and decerebrate rats, as were the dose-response relationships, indicating the caudal brainstem is sufficient for mediating response production. 33 Hypothalamic processing had been hypothesized to mediate the profile of responses evoked by peripheral GLP-1R ligand delivery.…”
Section: Glp-1mentioning
confidence: 82%
“…It was hypothesized that the actions of CCK may have been partly dependent on 5-HT 3 receptor activation; i.e., CCK may release 5-HT, which acts on 5-HT 3 receptors to inhibit RVLM neuronal activity. In examining the effects of CCK on feeding, many have suggested that the actions of CCK are partially dependent on 5-HT 3 receptor activation (1,6,14). Furthermore, primary vagal afferent neurons are potently stimulated by endogenous 5-HT and CCK release (26,53), and a subpopulation of nodose ganglion neurons possess high-affinity CCK 1 receptors and 5-HT 3 receptors (24).…”
Section: Discussionmentioning
confidence: 99%